Effects of high fructose and salt feeding on systematic metabonome probed via 1H NMR spectroscopy. (16th January 2015) - Yang, Yongxia; Zheng, Lingyun; Wang, Linlin; Wang, Shumei; Wang, Yaling; Han, Zhihui
Abstract : Diets rich in high fructose and salt are increasingly popular in our daily life. A combination consumption of excessive fructose and salt can induce insulin resistance (IR) and hypertension (HT), which are major public health problems around the world. However, the effects of high fructose and salt on systematic metabonome remain unknown, which is very important for revealing the molecular mechanism of IR and HT induced by this dietary pattern. The metabolic profiling in urine, plasma, and fecal extracts from high fructose and salt‐fed rats was investigated by use of 1 H nuclear magnetic resonance (NMR)‐based metabonomics approach in this study. Multivariate analysis of NMR data showed the effects of high fructose and salt on the global metabonome. The metabolite analysis in urine and fecal extracts showed the time‐dependent metabolic changes, which displayed metabonomic progression axes from normal to IR and HT status. The changes of 2‐oxoglutarate, creatine and creatinine, citrate, hippurate, trimethylamine N ‐oxide (TMAO), and betaine in urine, together with gut microbiota disorder in feces, were observed at the preliminary formation stage of IR and HT (fourth week). At the severe stage (eighth week), the previously mentioned metabolic changes were aggravated, and the changes of lipid and choline metabolism in plasma suggested the increased risk of cardiovascular diseases. These findings provide an overview of biochemistry consequences of high fructose and salt feeding and comprehensive insights into the progression of systematic metabonome for IR and HT induced by this dietary pattern. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This study identified the metabolic changes and potential biomarkers in urine, plasma, and feces of high fructose and salt‐fed rats using NMR‐based metabonomics.